2020
DOI: 10.3390/nano10081480
|View full text |Cite
|
Sign up to set email alerts
|

To-Do and Not-To-Do in Model Studies of the Uptake, Fate and Metabolism of Metal-Containing Nanoparticles in Plants

Abstract: Due to the increasing release of metal-containing nanoparticles into the environment, the investigation of their interactions with plants has become a hot topic for many research fields. However, the obtention of reliable data requires a careful design of experimental model studies. The behavior of nanoparticles has to be comprehensively investigated; their stability in growth media, bioaccumulation and characterization of their physicochemical forms taken-up by plants, identification of the species created fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Furthermore, the characteristics of AgNPs such as size, concentration, and charge [ 18 , 19 ] as well as the experimental conditions including duration and method of exposure [ 20 , 21 , 22 ] also play significant roles, influencing the stability of AgNPs and their susceptibility to transformation [ 19 , 23 ]. In recent studies, it was revealed that AgNP stability is also dependent on the composition and type of the exposure medium [ 24 , 25 ]. The use of various surface coatings in their synthesis influences the physiochemical properties of AgNPs, not only by reducing particle agglomeration and enhancing their stability but also by modulating toxic effects [ 4 , 18 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the characteristics of AgNPs such as size, concentration, and charge [ 18 , 19 ] as well as the experimental conditions including duration and method of exposure [ 20 , 21 , 22 ] also play significant roles, influencing the stability of AgNPs and their susceptibility to transformation [ 19 , 23 ]. In recent studies, it was revealed that AgNP stability is also dependent on the composition and type of the exposure medium [ 24 , 25 ]. The use of various surface coatings in their synthesis influences the physiochemical properties of AgNPs, not only by reducing particle agglomeration and enhancing their stability but also by modulating toxic effects [ 4 , 18 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A low pH media (e.g., pH 5.5 and lower) should be used with caution as the acidity causes dissolution of ENMs such as Ag, ZnO and CuO. 44 Wojcieszek, et al 45 provide some useful guidance on best practices for studies investigating metal ENM uptake in plants, including on how to prepare and perform spICP-MS. A typical protocol (Table 2) with this enzyme mixture for the extraction of ENMs will involve: (i) homogenization of leaf, shoot or root tissue in a buffer solution (pH 3.5-7), (ii) addition of macerozyme R-10 enzyme solution resulting in a final volume and enzyme concentration of 1-50 mL and 1-50 mg mL −1 respectively, and (iii) incubation for 24-36 hours at 37 °C. As above, the enzyme solutions used were reported as mass concentrations of powder used as opposed to enzyme activity.…”
Section: Enzyme-based Extraction Protocolsmentioning
confidence: 99%
“…In the past, the detection of nanomaterials in plant tissues provided contradictory results, partly due to the different detection techniques, nanomaterial transformation processes, nanomaterial sizes and properties, and experimental designs used in studies ( Montes et al , 2017 ; Wojcieszek et al , 2020 ). Nowadays, numerous methods are being used in nanomaterials research, which will be summarized briefly below.…”
Section: Behaviour Of Essential Nanometals On Root/leaf Surfaces and ...mentioning
confidence: 99%
“…The technique is limited due to the sample preparation method, since it can measure metal content only from acid-decomposed samples. A new technique, single-particle ICP-MS, has been developed, which is able to measure dissolved particles, and can measure each NP individually ( Wojcieszek et al , 2020 ). It is able to detect NP alterations, which is crucial information in samples.…”
Section: Behaviour Of Essential Nanometals On Root/leaf Surfaces and ...mentioning
confidence: 99%
See 1 more Smart Citation